2017
DOI: 10.1038/cddis.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-466 inhibits tumor growth and bone metastasis in prostate cancer by direct regulation of osteogenic transcription factor RUNX2

Abstract: MicroRNAs (miRNAs) have emerged as key players in cancer progression and metastatic initiation yet their importance in regulating prostate cancer (PCa) metastasis to bone has begun to be appreciated. We employed multimodal strategy based on in-house PCa clinical samples, publicly available TCGA cohorts, a panel of cell lines, in silico analyses, and a series of in vitro and in vivo assays to investigate the role of miR-466 in PCa. Expression analyses revealed that miR-466 is under-expressed in PCa compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 41 publications
3
99
0
Order By: Relevance
“…In this study, we showed that the expression of miR-466 was downregulated in CRC compared to matched adjacent normal tissues, suggesting that miR-466 may be associated with the progression and development of CRC. Similar results were reported on the role of miR-466 in PC [11].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, we showed that the expression of miR-466 was downregulated in CRC compared to matched adjacent normal tissues, suggesting that miR-466 may be associated with the progression and development of CRC. Similar results were reported on the role of miR-466 in PC [11].…”
Section: Discussionsupporting
confidence: 79%
“…Our results showed that the increased expression of miR-466 suppressed the proliferation, migration and invasion as well as induced apoptosis in CRC cells. Similar results were also reported in highly metastatic PC cells [11]. Overall, our results indicated that the overexpression of miR-466 impaired the oncogenic function in CRC cells, which may also explain the positive association between miR-466 downregulation and the tumor size, TNM stage, metastasis, and poor outcome.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Expression analyses demonstrated that miR‐466 was downmodulated in PCa relative to normal tissues. Newly Colden et al () dissected that in vitro upmodulation of miR‐466 in metastatic PCa cell lines diminished oncogenic features like cell proliferation, migration/invasion, and increased cell cycle arrest as well as apoptosis of tumor cells than control miRNA. Contrarily, depletion of miR‐466 in normal PCa cell lines increased tumorigenic behaviors.…”
Section: Mirna Associated With Cell Migration Invasion and Emtmentioning
confidence: 99%
“…It has been reported that miR-466 directly targeted RUNX2, which induced downregulation of RUNX-target genes involved in migration, invasion, EMT and metastasis. Overexpression of miR-466 in PC3 orthotopic xenografts greatly reduced the number of spontaneous bone metastases and improved mice overall survival (Colden et al 2017).…”
Section: Mirnas Associated To Pca Bone Metastasismentioning
confidence: 99%